Literature Review : Mengidentifikasi Kesadaran Diri Individu terhadap Pengaruh Pemerasan Emosional - Erlangga Hidra; Qirani Ajeng Pinasti; Supriyono (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
Emotional Blackmail is a powerful form of manipulation where people closest to us threaten, either directly or indirectly, with the aim of making us feel guilty and making us anxious if we don't do what they want. Emotional blackmail is a concept presented by psychologist Susan Forward in the book "Emotional Blackmail". The research method used is the Literature Review Study method using the book "Emotional Blackmail" by Zhou Mu-Zi. The purpose of this research is to determine the awareness of emotional blackmail experienced by several people from different perspectives in the book "Emotional Blackmail" by Zhou Mu-zi. The results of research from the books reviewed can be identified that many people fall into the cycle of emotional blackmail and few people are aware of emotional blackmail. This is proven by the impact and characteristics of emotional blackmail in several individual cases in the surrounding environment which were written and described in the book "Emotional Blackmail" based on true stories of victims who poured out their complaints to the author.